Distributed systems : concepts and design - Coulouris, George F. (International computer science series, 2012)
"[This] book aims to provide an understanding of the principles on which the Internet and other distributed systems are based; their architecture, algorithms and design; and how they meet the demands of contemporary distributed applications."--p. xii